The Role of Political Communication in Addressing Polarization and Identity Politics in Indonesian Democracy - Handoko, Gatot Repli; Swastiningsih, Swastiningsih (Penerbit Mandalika Indonesia, 2025)
Political polarization and the rise of identity politics have become major challenges in contemporary Indonesian democracy, particularly in the era of digital media and open political participation. The extensive use of religious, ethnic, and social identities in political communication has contributed to social fragmentation and weakened democratic deliberation. This study aims to analyze the role of political communication in addressing polarization and identity politics in Indonesia. The research employs a qualitative approach using a literature review method. Data were collected from peer-reviewed journal articles, academic books, and research reports related to political communication, polarization, identity politics, and Indonesian democracy. The collected literature was analyzed thematically to identify key patterns, strategies, and actors involved in political communication practices. The findings indicate that political communication plays a dual role: it can intensify polarization when dominated by confrontational and identity-based narratives, but it can also reduce social division when practiced in an inclusive, dialogical, and constructive manner. Inclusive political communication that emphasizes shared values, democratic norms, and public interests is found to be effective in mitigating polarization and strengthening social cohesion. The study concludes that ethical and responsible political communication is essential for consolidating democracy in Indonesia.